PENGARUH MOTIVASI BELAJAR SISWA DALAM MEMILIH GEOGRAFI SEBAGAI PROGRAM LINTAS MINAT TERHADAP HASIL BELAJAR SISWA DI SMAN 8 PADANG - Teguh Mulia; Sri Mariya (JURNAL BUANA, 2023)
This study aims to determine the effect of learning motivation and students' decisions in the MIPA (Mathematics and Natural Sciences) family in choosing a cross-interest geography program on learning outcomes at SMA Negeri 8 Padang. This research is motivated by the existence of educational programs that require students to choose cross-interest programs that they did not study in their home major. This type of research is a quantitative research. The population and sample in this study were students of Class X MIPA 4 and X MIPA 5 at SMA Negeri 8 Padang in the 2021/2022 academic year. The sampling technique in this study used the Total Sampling technique, which was 68 respondents. Data analysis used a Likert scale using the IBM SPSS 25 program and assisted by Microsoft Excel to process the data. The data testing technique uses multiple linear analysis. The results of this study indicate that learning motivation has a positive and significant influence on student learning outcomes with a t-count value (3.431) > t-table (1.99714) with a significant level of 0.004 <0.05